Genetic diversity in eggplant genotypes for heat tolerance (SAARC Journal of Agriculture, 2015)
Genetic divergence in eighteen eggplant genotypes was studied at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Salna, Gazipur, Bangladesh during February 2007 to December 2008 using multivariate analysis. Eggplant genotypes were evaluated for different quantitative characters. Among the genotypes wide variations were observed for plant, flower and fruit size, shape and color. Out of 18 genotypes only 8 were found to be suitable for summer and summer rainy season cultivation as heat tolerance. The 18 genotypes were grouped into four distinct clusters. Cluster I comprised of 2 genotypes, cluster II had 3, cluster III had 3 and cluster IV had 10 genotypes. Clustering pattern of the genotypes was not correlated with their geographical distribution. The highest inter cluster distance was between cluster I and IV (764.67) while, it was the lowest between cluster II and III (213.30). The highest and lowest intra cluster distance was displayed in cluster II (94.14) and cluster I (28.79) respectively. Yield per plant, number of fruits per plant, plant canopy, fruit weight, fruit length and number of harvest had the highest contribution towards total divergence. Moderate to high Shannon-Weaver Diversity Indices (SWDI) was found among the genotypes for most of the studied qualitative characters. Quantitative vegetative characters had high diversity among the genotypes, while it was moderate to high diversity for both flower and fruit characters. Eight eggplant genotypes were selected as heat tolerance based on genetic diversity of morphological characters in eggplant. DOI: http://dx.doi.org/10.3329/sja.v12i2.21914 SAARC J. Agri., 12(2): 25-39 (2014)